Psychometric validation of the Stoma-QOL questionnaire in a Canadian cross-sectional sample of colostomy and ileostomy patients. (3rd June 2018) - Lai, Ernest; Peterson, Alexander Caston; Liu, Guiping; Karimuddin, Ahmer; Crump, R. Trafford; Sutherland, Jason M.
Abstract: Objectives: The Stoma-QOL questionnaire is a patient-reported outcome (PRO) used to measure quality of life in patients with ileostomy or colostomy. This study assesses the Stoma-QOL's overall and item-level psychometric characteristics in patients with temporary stomas, and whether stoma-related quality of life differs by demographic characteristics. Materials and methods: Analysis of cross-sectional observational PRO data from hospitals in Vancouver, Canada. Patients registered for elective ileostomy or colostomy closure, over the age of 18, and able to read English were eligible for participation. Emergent and cancer-related cases were excluded. One-way analysis of variance was used to test for demographic differences in Stoma-QOL scores. Cronbach's alpha was used for reliability, and Rasch item-response theory was used to assess overall and item characteristics. Results: 120 patients were included. No statistically significant difference in Stoma-QOL scores was found by age, sex, or socioeconomic status. Reliability was 0.93. Mean item responses ranged from 1.77 to 3.55 and item-total correlation ranged from 0.51 to 0.77. The Rasch item-response theory model demonstrated significant misfit, likely due to the misfit of item 9, which asks about sexuality, and high residual correlations between item pairs 6 and 8 about fatigue, and items 16 and 17 about social relationships. Conclusions: The Stoma-QOL questionnaire is a well-designed PRO for measuring stoma-related quality of life. Demographic variables do not appear to have a strong influence on Stoma-QOL scores. Item 9 demonstrated misfit but removal likely does not improve the instrument. Future research should focus on revising items 6, 8, 16, and 17.